2131. A Pre-operative Nursing Implemented Methicillin-resistant Staphylococcus aureus Decolonization Protocol to Decrease Surgical Site Infections. (26th November 2018) - Schmidt, Melissa; Stewart, Christy; Forrest, Graeme N; Pfeiffer, Christopher; Atherton, Sherri
Abstract: Background: Surgical site infections (SSIs) are the most common and expensive healthcare-acquired infection. Implementation of processes to prevent SSI can be difficult due to coordination of patients, providers, pharmacists, and nurses in ensuring all steps are completed before surgery. Thus, the objective of this nurse-driven process improvement project at a veterans affairs (VA) hospital, which averages 6, 000 simple to complex surgeries per year, was to implement a cost-effective and practical decolonization protocol to decrease methicillin resistant Staphylococcus aureus (MRSA) SSIs across all surgical case types. Methods: Starting May 15, 2017 a new MRSA decolonization protocol was initiated for ALL surgery cases except eye. Pre-operative clinic nurses complete MRSA nasal screening and provide detailed pre-operative showering instructions which include a focus on preventing recontamination of the skin after showers. Before surgery, nurses provide intranasal Povidone-Iodine treatment. The surgery pharmacist ensures MRSA postive patients receive pre-operative vancomycin and cefazolin if antibiotics are indicated for the surgery. Results: For fiscal years (FY) 2012–2016 prior to protocol implementation, annual MRSA SSI rates ranged from 0.24–0.11 SSIs per 100 surgery cases; the average SSI rate for this time period 0.17. After protocol implementation there were zero MRSA SSIs in FY17 quarter 3 lowering the FY17 SSI rate to 0.09 SSIs per 100 surgery cases (see Figure 1.) Since implementation only 1 MRSA SSI has been identified making the last 4 quarter SSI rate 0.04 per 100 surgery cases (see Figure 2). This represents a 76% improvement in the 1 year MRSA SSI rate (0.04) compared with the previous 5 years MRSA SSI rate average. Conclusion: Initial protocol results suggest that practical nursing interventions should be considered for implementation to decrease MRSA surgical site infections. Disclosures: All authors: No reported disclosures.